PENGARUH MODEL PEMBELAJARAAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER BERBANTUAN GEOGEBRA TERHADAP HASIL BELAJAR MATEMATIS PESERTA DIDIK DI KELAS VIII SMP NEGERI 43 PADANG - Hastuti, Yuliana Fitriani; Dwina, Fitrani (Departemen Matematika, 2024)
Getting good learning outcome is an important thing for the student Because it can be stated as achievement indicators in developing knowledge according to what they have been studied. In the reality mathematics learning outcomes that was obtained by class VIII students at SMP Negeri 43 Padang are still very low. Many of them have not been active involved in mathematics learning. To overcome this problem, the model of Numbered Heads Together (NHT) learning was implemented by the purpose to finding out whether the outcomes of learning in mathematics by students who studied with the NHT model supported by Geogebra were better than learning which conventional. The research type is quasi-experiment with a nonequivalent posttest-only control group design. The research were student in class VIII of SMP Negeri 43 Padang for the 2023/2024 learning year. Based on data analysis, the student learning outcomes using the NHT model assisted by Geogebra are better than conventional learning.keywords- Numbered Heads Together, Learning Outcomes, Cooperative Learning Model